If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 6 = 6 + -1x Reorder the terms: 6 + 3x = 6 + -1x Add '-6' to each side of the equation. 6 + -6 + 3x = 6 + -6 + -1x Combine like terms: 6 + -6 = 0 0 + 3x = 6 + -6 + -1x 3x = 6 + -6 + -1x Combine like terms: 6 + -6 = 0 3x = 0 + -1x 3x = -1x Solving 3x = -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 3x + x = -1x + x Combine like terms: 3x + x = 4x 4x = -1x + x Combine like terms: -1x + x = 0 4x = 0 Divide each side by '4'. x = 0 Simplifying x = 0
| p^2-12p+45=0 | | x^2+2x^2-900=0 | | 4/25•2/5= | | 4(2x+5)=-17+5 | | 1 = c2 | | q+7=9 | | 7r=60-5R | | 3 = d2 | | 7-4(4-(3y-7))=0 | | F(4)=x+9 | | 16y^3/20y^4 | | -45=-3x+18 | | 5a^2-a-20=0 | | -7/2x=-28 | | 3w^2-7w=6 | | (x-1+3i)(x-1-3i)=0 | | -3(5x+6)=-84 | | 1:1000/1:100×250 | | -4(-5x+6)=84 | | 2t=t+15 | | -6(3x-8)=102 | | 6-3x=9x | | -15-3x=-6x+27 | | 1/c=0.15 | | 6x-10=14+2x | | (s-4)(2s+2)(s^2-2)= | | 5x-34=74-4x | | 162x-82=738 | | 4(3n+3)=7(6n+7)+1 | | -162x-82=738 | | x-36=-4x+39 | | 11x+11y=-88 |